Role of genetic research in the prevention of life-threatening rhythm and cardiac conduction disorders in young people - E. N Loginova; E. A Kirh; G. I Nechaeva; A. I Martynov; I. V Druk; A. A Semenkin; A. N Dakuko (Российский кардиологический журнал)
According to epidemiological studies, in Russia there is a tendency towards an increase in sudden cardiac death (SCD), including among young workingage people. The leading mechanism for SCD in young patients, including those with undifferentiated connective tissue disease, is recognized as rhythm and conduction disorders. At the same time, the most tragic cases are the first and only manifestation of SCD in children and young people without structural heart disease. The article presents a brief analysis of the genetic causes of life-threatening rhythm and conduction disorders in young people, as well as a generalization of the modern possibilities of a personalized diagnostic approach from the standpoint of early cardiovascular prevention. Timely genetic diagnosis of SCD risk makes it possible to identify a predisposition to the development of a fatal event long before its occurrence, which contributes to the timely implementation of preventive measures within a high cardiovascular risk strategy and secondary prevention, maintaining working capacity, creative and social activity of young patients, and improving the quality of life.